2017
DOI: 10.14202/vetworld.2017.1286-1291
|View full text |Cite
|
Sign up to set email alerts
|

Survivin expression in canine spontaneous cutaneous and subcutaneous tumors and its prognostic importance

Abstract: Aim:The present study was carried out to know the expression level of survivin, an inhibitor of apoptosis protein with an objective to determine its prognostic importance in cutaneous and subcutaneous tissue tumors of dogs.Materials and Methods:Forty cases of canine cutaneous and subcutaneous tissue tumors on histopathological examination revealed various round cell, epithelial, and mesenchymal cell tumors. Survivin gene expression was detected in all tumors tested by TaqMan real-time polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…The prognostic relevance of survivin has been investigated in humans, associated higher survivin concentrations with a poor prognosis and lower survival rates [ 1 8 28 ]. In veterinary medicine, the prognostic relevance of survivin was investigated primarily for osteosarcoma and cutaneous and subcutaneous tissue tumors, showing mixed results depending on the tumor entity [ 17 18 ]. Based on the follow-up information in approximately 16% of the dogs in the present study, there was no correlation between the serum survivin concentration and the outcome of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic relevance of survivin has been investigated in humans, associated higher survivin concentrations with a poor prognosis and lower survival rates [ 1 8 28 ]. In veterinary medicine, the prognostic relevance of survivin was investigated primarily for osteosarcoma and cutaneous and subcutaneous tissue tumors, showing mixed results depending on the tumor entity [ 17 18 ]. Based on the follow-up information in approximately 16% of the dogs in the present study, there was no correlation between the serum survivin concentration and the outcome of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Research into biomarkers in veterinary medicine has become a focus and could have the potential for veterinary oncology. Most studies examined the appearance of survivin in tissues, which usually requires invasive investigatory methods [ 17 18 ]. Only a few studies have evaluated the survivin concentrations in the sera of tumor-bearing dogs [ 19 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an additional study [62], nuclear survivin was also detected in 50% of cystitis tissues whereas cytoplasmic survivin was only detected in 8% of these tissues. In 2017, a study comparing canine tumors of different origins (epithelial, mesenchymal and round-cell tumors) showed that survivin was significantly increased in malignant versus benign tumors (p < 0.05) at the transcriptional level [64]. Finally, in 2020, the survivin inhibitor EZN-3042 was shown to be well-tolerated in a phase I clinical trial of dogs with lymphoma, opening new avenues for the clinical targeting of this protein in veterinary oncology [65].…”
Section: Evasion Of Apoptosis-the Role Of Survivinmentioning
confidence: 99%
“…Survivin is a bi-functional protein that promotes cell growth by inhibiting apoptosis. It is overexpressed in many cancers including breast [ 11 ], esophagus [ 12 ], lung [ 13 ], lymphoma [ 14 ], and others [ 15 17 ]. CXCR4 is a chemokine receptor that is expressed on most hematopoietic cells [ 18 ].…”
Section: Introductionmentioning
confidence: 99%